A Qualitative Study on Business Performance in Turbulent Environment - Naseem, Aliya; Abbas, Rameesha (Archives of Business Research, 2022)
The combination of business strategies and practices that tends to enhance sustainability of performance has been the subject of only a modest number of scholarly studies, but has been at the forefront of corporate agendas for decades. Dramatic shifts in performance and industry standing occur frequently among firms that develop technology products and services, the ‘technology innovators,’ in part because these firms operate in external business environments that tend to be turbulent. This exploratory study focuses on the integration of these five elements through case studies of three medium to large technology innovator firms operating under medium or high environmental turbulence. Interviews of 10 managers, directors and executives based on a semi-structured guide were augmented by qualitative self-assessment of leadership style, a validated instrument for assessing culture type, pre-interview surveys and secondary data. The results are: a single predominant leadership style setting an expectation of high performance was seen among managers in all three firms, a high presence of Aggressive/Defensive cultural style existed among the firms, and sustainability of performance was believed by interviewees to depend on effective integration of strong leadership style and culture, structure appropriate for innovation, and balanced emphasis on strategic positioning and operational effectiveness.